G-protein αq gene expression plays a role in alcohol tolerance in Drosophila melanogaster. (November 2019) - Aleyakpo, Benjamin; Umukoro, Oghenetega; Kavlie, Ryan; Ranson, Daniel C.; Thompsett, Andrew; Corcoran, Olivia; Casalotti, Stefano O.
Ethanol is a psychoactive substance causing both short- and long-term behavioural changes in humans and animal models. We have used the fruit fly Drosophila melanogaster to investigate the effect of ethanol exposure on the expression of the Gαq protein subunit. Repetitive exposure to ethanol causes a reduction in sensitivity (tolerance) to ethanol, which we have measured as the time for 50% of a set of flies to become sedated after exposure to ethanol (ST50). We demonstrate that the same treatment that induces an increase in ST50 over consecutive days (tolerance) also causes a decrease in Gαq protein subunit expression at both the messenger RNA and protein level. To identify whether there may be a causal relationship between these two outcomes, we have developed strains of flies in which Gαq messenger RNA expression is suppressed in a time- and tissue-specific manner. In these flies, the sensitivity to ethanol and the development of tolerance are altered. This work further supports the value of Drosophila as a model to dissect the molecular mechanisms of the behavioural response to alcohol and identifies G proteins as potentially important regulatory targets for alcohol use disorders.